Time-dependent reliability of strengthened PSC box-girder bridge using phased and incremental static analyses. (15th June 2016) - Guo, Tong; Chen, Zheheng; Liu, Tie; Han, Dazhang
Highlights: Time-dependent reliability of strengthened PSC box-girder bridges is studied. A probabilistic finite element approach is introduced to consider the uncertainty. Phased analysis is used to account for the existing damage prior to strengthening. An incremental static analysis method is adopted for reliability analysis. Abstract: Prestressed concrete (PSC) box-girder bridges are extensively used in highway and railway construction. Excessive long-term deflection and unexpected cracks however are often observed. To achieve deflection control and/or to restore the bearing capacity of bridges, structural strengthening measures are frequently adopted. This paper proposes an approach based on probabilistic finite element analyses to evaluate the time-dependent reliabilities of strengthened PSC box-girder bridges. The time-dependent behaviour of the girders is simulated considering concrete shrinkage, creep and cracking, corrosion and stress relaxation of steel, etc. In particular, phased analysis is adopted to account for the existing damage and stress conditions prior to strengthening, and the incremental static analysis method is used to calculate the structural reliabilities. Application is made to the time-dependent reliability assessment of a PSC box-girder bridge, and the effectiveness of three strengthening methods including externally bonded steel plates, fibre reinforced polymer (FRP) composites and external post-tensioning is compared. The presented study provides references to reliability-based design and optimization of strengthening strategies for PSC box-girder bridges.